Deliberate ignorance : choosing not to know - Hertwig, Ralph,; Engel, Christoph, 1956- (Strüngmann forum reports, 2020)
"Psychologists, economists, historians, computer scientists, sociologists, philosophers, and legal scholars discuss when is deliberate ignorance a virtue, and what type of environment does it require"--